(3GdfgQ GdLGQi aj TQM GdHNGQis - (3HgGA GdOjf YHO GdcQje Hf eMH GdOjf Hf CHi YjSi CMeO Hf eMeO GdYOfi GdgfOi GdMfaj GdeYQha HGdbWHis; (3CHh YHO Gddg eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, GdEeGe GdHNGQj,J (B256 (3g` s
(3ChdgG (B:s
(3cJGH GdLeYI ef GdELJeGY CVja Edjg Gdjhe hGdUdGI , Ke cKQ GdESJYeGd , MJi MPa efg GdUdGI , hge HVe GdLje hGdeje s
(3BNQgG (B:s
(3jfJgi HHGH SLOI U s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ HYV YHGQGJgG HGdMeQI MhGa HYV ChQGbgG eJbUaI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdMOjK h GdeUWdMs